Demand and Production Management Systematics for Optimizing the Fulfillment of Tempe Demand in MSMEs Mantab Rasa Madiun City - Dian Indrawati, Chatarina; Paulus, Ardianus Laurens; Murdapa, Petrus Setya (Fakultas Ekonomi dan Bisnis Universitas Negeri Jakarta, 2021)
Mantab Rasa Madiun is a home-based business in the city of Madiun that manages and supplies soybean tempe products with a capacity of 150-200 kg of soybeans per day. Providing product availability in the market is quite a complicated issue for Mantab Rasa, especially for food products that have a perishable product life. The delay in conveying information to the production department causes the accuracy of the production quantity to be unsuccessful so that many requests cannot be fulfilled or products that are not absorbed. Strategies to solve the problem include the formulation of a method of identifying market demand per day so that the response of the production section to meet demand is almost accurate. The method offered is to collect demand data from sales through the WA group so that the demand data can be centralized and easy to enter into the forecasting application formulation of demand data then forecast with an MS Excel-based application. From the forecasting results, it is then included in the MRP-Like time phasing formula with the aim that operational managers can more easily decide how many kg of raw and soaked soybeans to boil today. The systematics that have been made have been socialized to partners and tested for 7 days. The results obtained are the managers have a recapitulation of centralized daily demand data and quickly get a decision on how much soybeans are processed to meet demand.